Zróżnicowanie atrakcyjności lokalizacji w mieście na przykładzie łódzkiego rynku nieruchomości gruntowych - Sokołowicz, Mariusz P. (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The situation that exists on the real estate market is one of the most important elements of local economy. The functions and local "embedness" of the real estate market occurred as a motivation for the analysis of some transactions that appear on the market of this kind. However, quite high degree of confidence as a typical characteristic of real estate market, is a significant barrier for the research. Despite of this situation, some attempt to investigate this field of local economy, can be undertaken.The article is a proposition of the research of the transactions of grounds (non-built areas) in the City of Lodz, preceded by presentation of the specifity of this part of the real estate market and factors that influence the price of the building lots as well. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 349-357